(untitled) (CIPEEX, 2022)
ANTERIOR CRUCIATE LIGAMENT (ACL) RUPTURE IS FREQUENT IN SPORTS PRACTICES, OCCURRING MOSTLY IN MALES. THIS LESION CAUSES CHRONIC INSTABILITY OF THE JOINT, SO ITS RECONSTRUCTION IS IMPORTANT, EITHER SURGICALLY, IN THE MAJORITY OF CASES, OR BY THE CONSERVATIVE METHOD. THE CASE REPORT SHOWS A RARE SITUATION IN WHICH THE PATIENT PRESENTED COMPLETE RUPTURE OF ACL REGENERATED WITHOUT SURGICAL INTERVENTION AFTER 7 MONTHS. AT THE PHYSICAL EXAMINATION, THE PATIENT PRESENTED STABILITY IN THE RIGHT KNEE, WITH ALL THE NEGATIVE TESTS FOR ACL LESION, CONFIRMED BY MAGNETIC RESONANCE IMAGING (MRI). THE RELEVANCE OF THIS CASE IS DUE TO THE FACT THAT MOST OF THE TIME A SURGICAL INTERVENTION IS NECESSARY TO RECOMPOSE THE ACL, SINCE SEVERAL FACTORS HINDER THE SPONTANEOUS REGENERATION OF THE CONTUSION. THE LITERATURE SHOWS THAT IN CASES OF COMPLETE ACL INJURY, SURGERY IS THE BEST OPTION, AND NON-SURGICAL TREATMENT, THAT IS, CONSERVATIVE, IS MORE APPROPRIATE FOR CASES OF PARTIAL RUPTURE AND IS MAINLY AIMED AT ANALGESIA AND DYNAMIC STABILIZATION OF THE KNEE, BY MEANS OF PHYSIOTHERAPEUTIC TREATMENT THAT HAS THE OBJECTIVE TO INCREASE THE RANGE OF MOVEMENT AND TO STRENGTHEN THE MUSCLES. FAILURE TO TREAT THE LESION MAY RESULT IN WORSENING OF THE CLINICAL PICTURE, WITH IMPAIRED MOTOR FUNCTION. HOWEVER, THE REPORTED CASE DIVERGES FROM THIS PERSPECTIVE, SINCE, WITHOUT THE INDICATED TREATMENT, THE PATIENT HAD A COMPLETE SPONTANEOUS ACL REGENERATION, AND FOR THIS REASON CONSERVATIVE TREATMENT SHOULD BE FURTHER STUDIED TO BETTER UNDERSTAND CASES LIKE THIS.